Understanding the process that gives rise to household car ownership level changes. (July 2016) - Clark, Ben; Lyons, Glenn; Chatterjee, Kiron
Abstract: Quantitative studies have revealed that changes to the number of cars owned by households are more likely to occur at the time of life events. However, causal explanations of such relationships are either absent or lacking evidence. To address this knowledge gap, this paper presents a qualitative study which enabled the development of a new conceptual framework to explain the process through which the number of cars owned by households changes over time. The framework emerged through an inductive analysis of 15 in-depth biographical interviews and was validated through a mixed methods survey of 184 households located in Bristol (UK). The following mechanisms of the process are identified: Life events alter roles, relationships, spatial contexts and lifestyle preferences. This can lead to a condition of stress which relates to a discrepancy between satisfaction with the current car ownership level and a more desirable alternative. Attempts to adjust to the new situation are made through processes of travel behaviour adaptation and consideration of whether the car ownership level ought to be altered. A propensity to change car ownership level can emerge from this. However, given the effort involved in taking action, households tend to resist making changes to their car ownership level in the short term. Action to change car ownership level is found to often be prompted by another external stimulus such as the receipt of a maintenance bill. A key message from the analysis is that changes in household car ownership level should be considered as the outcome of a continuous process of development over the life course, rather than as discrete decisions. Highlights: Qualitative methods to explain changes in household car ownership over time Car ownership changes are viewed as a process rather than as discrete decisions. Car ownership changes are shown to be related to life events. Life events alter roles, relationships, spatial contexts and lifestyle preferences. Behavioural adaptation/consideration alters the potential for car ownership change.